2006
DOI: 10.1016/s0022-5347(05)00416-7
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Urinary Symptoms Predict Adult Overactive Bladder Symptoms

Abstract: Purpose-A relationship between childhood urinary symptoms and adult lower urinary tract symptoms in women is often clinically suspected. In this analysis we investigated the relationship between childhood and adult urinary symptoms in middle-aged women.Materials and Methods-A population based cohort of 2,109 women 40 to 69 years old who were members of a large health maintenance organization was randomly selected from age and race strata. Through self-reported questionnaires, women recalled a childhood history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
85
2
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(97 citation statements)
references
References 21 publications
4
85
2
6
Order By: Relevance
“…[23][24][25][26][27] Classifications for urinary incontinence and nocturia are consistent with the definitions developed by the International Continence Society. 28 UTI was assessed using the question, ''How many times have you been told that you had a urinary tract infection in the past 6 months?''…”
Section: Methodsmentioning
confidence: 89%
“…[23][24][25][26][27] Classifications for urinary incontinence and nocturia are consistent with the definitions developed by the International Continence Society. 28 UTI was assessed using the question, ''How many times have you been told that you had a urinary tract infection in the past 6 months?''…”
Section: Methodsmentioning
confidence: 89%
“…Diurnal urinary incontinence and nocturnal enuresis in childhood double the risk of urge incontinence in adulthood [37]. Another retrospective study of 170 women found a high prevalence of LUTD during childhood in women with the following symptoms: increased urinary frequency, urgency, stress incontinence, and urge incontinence [38].…”
Section: Discussionmentioning
confidence: 99%
“…L'hypothèse d'un dysfonctionnement du SNA à l'état basal, vessie vide, peut donc être évoquée dans le SCHV idiopathique. De plus, il existe un continuum entre l'énurésie nocturne de l'enfant et le SCHV idiopathique dans environ un tiers des cas [16] ; un continuum physiopathologique est donc possible.…”
Section: Discussionunclassified